# 9(b-4)-7=5(3b-2)

## Simple and best practice solution for 9(b-4)-7=5(3b-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 9(b-4)-7=5(3b-2) equation:

Simplifying
9(b + -4) + -7 = 5(3b + -2)
Reorder the terms:
9(-4 + b) + -7 = 5(3b + -2)
(-4 * 9 + b * 9) + -7 = 5(3b + -2)
(-36 + 9b) + -7 = 5(3b + -2)
Reorder the terms:
-36 + -7 + 9b = 5(3b + -2)
Combine like terms: -36 + -7 = -43
-43 + 9b = 5(3b + -2)
Reorder the terms:
-43 + 9b = 5(-2 + 3b)
-43 + 9b = (-2 * 5 + 3b * 5)
-43 + 9b = (-10 + 15b)
Solving
-43 + 9b = -10 + 15b
Solving for variable 'b'.
Move all terms containing b to the left, all other terms to the right.
Add '-15b' to each side of the equation.
-43 + 9b + -15b = -10 + 15b + -15b
Combine like terms: 9b + -15b = -6b
-43 + -6b = -10 + 15b + -15b
Combine like terms: 15b + -15b = 0
-43 + -6b = -10 + 0
-43 + -6b = -10
Add '43' to each side of the equation.
-43 + 43 + -6b = -10 + 43
Combine like terms: -43 + 43 = 0
0 + -6b = -10 + 43
-6b = -10 + 43
Combine like terms: -10 + 43 = 33
-6b = 33
Divide each side by '-6'.
b = -5.5
Simplifying
b = -5.5`